Crystallographic feature of hydrogen-related fracture in 2Mn-0.1C ferritic steel. (14th June 2018) - Okada, Kazuho; Shibata, Akinobu; Takeda, Yasunari; Tsuji, Nobuhiro
Abstract: The present paper investigated crystallographic feature of hydrogen-related fracture in a 2Mn-0.1C steel having a simple ferritic microstructure. We found that the mechanical properties (in particular post-uniform elongation) were degraded by concurrent hydrogen-charging. Most of the fracture surfaces (over 90%) of the concurrently hydrogen-charged specimens showed quasi-cleavage morphologies with serrated markings, but no intergranular fracture surface was observed. Through a detailed crystallographic orientation analysis using EBSD, we have clarified that micro-cracks formed at ferrite grain boundaries and the micro-cracks propagated inside grains along crystallographic {011} planes of ferrite, leading to the quasi-cleavage fracture. Hydrogen micro-print technique revealed that hydrogen accumulated along ferrite grain boundaries under tensile-loading. On the basis of the obtained results, we propose that the fracture on {011} planes is an intrinsic characteristic of hydrogen-related quasi-cleavage fracture in steels having BCC phases. Highlights: Crystallographic features of hydrogen-related fracture in ferritic steel were investigated. Hydrogen pre-charging did not induce hydrogen-related fracture. Hydrogen concurrent charging degraded mechanical properties. Hydrogen tended to accumulate along grain boundaries during tensile-loading. Hydrogen-related quasi-cleavage fracture occurred on crystallographic {011} plane.